Chapter Unmanned Ground and Aerial Robots Supporting Mine Action Activities - Doroftei, Ioan (InTechOpen, 2017)
Lightweight protective structures and materials such as the personal protective equipment (PPE) for explosive ordnance disposal (EOD) personnel are frequently under investigation globally. Their mechanical response to impulsive loads such as blast and ballistic impacts is critical for establishing the spectrum of their performance against various types of threats. This chapter presents a novel testing technique that incorporates three near-simultaneous impacts in one shot in order to acquire deeper understanding of the dynamic interactions that take place during an explosion. A numerical model of an aramid fabric is developed to examine the parameters that influence the ballistic performance under multiple impacts. Fragment cluster impacts with dense dispersion have increased probability to perforate the target material. Heterogeneous, non-isotropic materials, like most of the ballistic grade protective materials, distribute the energy of the impacts in the form of stress wave streams causing the material to behave differently depending on the formation of the impacting fragments. Experimental work with aramid fabrics against single and triple impacts with the fragment-simulating projectile (FSP, 1.102 g) indicates that the ballistic limit in triple impacts is considerably lower that the ballistic limit in single impacts. The actual ballistic performance against multiple fragment impacts is severely underestimated with the classical single-impact methodologies.